Speech act as basis for dialoguecoherence : a case of English–Yoruba translation - Yekeen, Bello; B. M., Tunde-Awe; Folakemi Oyeniyi, Adeniyi-Egbeola (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study analysed speech act as a basis for dialogue coherence in English language and its relative translation unit in Yoruba language. The study viewed speech act theory as it dealt with functions and uses of language since it is said that speech acts are all the acts we perform through speaking. The study dealt with how speech act theories apply to English language dialogue and its translating equivalence in Yoruba language. The study modified and reframed Searle’s felicity conditions according to the categories of speech act to suit this study. The study hypothesised that speech acts in English language can be relatively translated into Yoruba language despite their cultural and systematic divergences between the two languages. The finding showed that both languages used a variety of patterns of speech acts among others in theirs dialogues which eventually revealed that speech act is a basis for dialogue coherence.